DAMPAK PERJANJIAN PERDAGANGAN BARANG ASEAN-KOREA FTA (AKFTA) TERHADAP INDONESIA DAN KOREA SELATAN - Setiawan, Sigit (Badan kebijakan Fiskal, 2012)
Preferential tariff scheme on ASEAN-Korea Free Trade Area (AKFTA) Trade Agreement in Goods have been above four years after its entry info force on July 1, 2007, as stated in Minister of Finance Decree Number 131/PMK011/2007. Its impact assessment should be conducted to review the expected gains for Indonesia and its country partner, South Korea from joining the agreement. This study employed a quantitative approach to measure and analyze the gains received by the two countries in AKFTA Trade Agreement in Goods from the increase of export growth and export contribution to national income. From the forecasting model employed, it showed that Indonesia gained more than Korea from AKFTA.